Back-end scheduling methods of virtual clusters for energy conservation in event-driven WSNs. (2017) - Chen, Haibao; Zhao, Yuyan; Zhao, Shenghui; Chen, Guilin
As sensor nodes of wireless sensor networks (WSNs) are generally battery-powered devices, the critical aspects to face concern how to conserve the energy for nodes, so that the network lifetime can be extended to reasonable times. In this paper, we aim at the energy conservation in event driven WSNs from the perspective of back-end scheduling for virtual clusters in cloud. Taking the Xen Credit scheduler as a baseline, we carry out a comparative study of three representative approaches (i.e., hybrid co-scheduling, balance scheduling, and dynamic switching-frequency scaling (DSS)). Then we discuss challenges in further optimising the energy conservation from the scheduling of virtual clusters. At last, we present and evaluate our proposed approach. Experimental results show that our approach outperforms the existing scheduling approaches of virtual clusters in the terms of reducing the energy consumption of WSNs.